(untitled) (Applied Biological Research, 2024)
The present study was aimed to evaluate the antifungal and antioxidant properties of leaf and fruit extracts of guava (Psidium guajava Linn.). Antifungal assays were conducted to assess the efficacy of extracts against clinically relevant fungal strains, viz., Aspergillus niger MTCC-4325, Penicillium chrysogenum MTCC-2539, Candida albicans MTCC-7315, and Fusarium solani MTCC-3309. Besides, enzyme activity for catalase (CAT) and peroxidase (POD) were assayed to elucidate the antioxidant potential of extracts. The radical scavenging activities of extracts were determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH), and ferric reducing antioxidant power (FRAP) assays to quantify the overall antioxidant capacity. Results indicated pronounced inhibitory activity against F. solani in methanolic extracts of leaves (21.66 ± 2.05) and fruits (24.66 ± 1.25), with aqueous extracts exhibiting comparatively lesser inhibition across the tested fungal strains. Moreover, the enzyme activity assays revealed higher CAT and POD activities in fresh leaf extract as compared to the fruit extract. Notably, DPPH assay underscored the superior antioxidant potential of Psidium leaf extracts relative to fruit extracts, while FRAP assay showed higher radical scavenging capacity of methanolic extract as compared to the aqueous extract.